Exacerbation of atherosclerosis, hyperlipidemia and inflammation by MK886, an inhibitor of leukotriene biosynthesis, in obese and diabetic mice - Katherine Keever; Bardia Askari (Elsevier, 2024)
Leukotrienes are potent mediators of the inflammatory response and 5-lipoxygenase, the enzyme responsible for their synthesis, is dependent on its interaction with 5-lipoxygenase activating protein for optimum catalysis. Previous studies had demonstrated that macrophage infiltration into adipose tissue is associated with obesity and atherosclerosis in LDLR−/− mice fed a high fat-high carbohydrate. The present study was undertaken to determine whether inhibition of 5-lipoxygenase activating protein is efficacious in attenuating adipose tissue inflammation in LDLR−/− mice fed a high fat-high carbohydrate. 10-week old male LDLR−/− mice were fed a high fat-high carbohydrate diet for 22-weeks, with or without MK886 (40 mg/kg/day, ad libitum) a well-established 5-lipoxygenase activating protein inhibitor. All mice had an approximate 2-fold increase in total body weight, but a 6-week course of MK886 treatment had differential effects on adipose tissue size, without affecting macrophage accumulation. MK886 exacerbated the dyslipidemia, increased serum amyloid A content of high-density lipoproteins and caused a profound hepatomegaly. Dyslipidemia and increased serum amyloid A were concomitant with increases in atherosclerosis. In conclusion, MK886 paradoxically exacerbated hyperlipidemia and the pro-inflammatory phenotype in a mouse model of diet-induced atherosclerosis, possibly via a disruption of hepatic lipid metabolism and increased inflammation.